Analisis Efisiensi Dan Efektivitas Pengelolaan Keuangan Daerah Kabupaten Tolikara - Yeperson Narek; Westim Ratang; Jhon U. Blesia (Journal of Innovative and Creativity, 2026)
The study purpose was. This study aims to analyse the efficiency, effectiveness, and optimisation efforts of regional financial management in Tolikara Regency during the period 2015–2022. Materials and methods. The assessment was carried out through an analysis of efficiency and effectiveness ratios based on a comparison between revenue realisation, expenditure realisation, and budget targets, and was reinforced with qualitative data from interviews with local financial management officials. Results. The results showed that regional financial management in Tolikara Regency was not yet optimal. The main obstacles affecting financial performance included: slow court proceedings and APBD (Regional Budget) determination, delays in DPA (Regional Budget Allocation) distribution, internet network constraints, and geographical challenges that hampered communication and financial reporting. The average level of efficiency in regional financial management during the research period was 95.15%, indicating that performance was in the inefficient category, as expenditure realisation was relatively high compared to revenue. Meanwhile, the average level of effectiveness was 90.49%, which is in the effective category, although it did not reach the ‘highly effective’ standard (≥100%). Conclusions. Efforts to optimise PAD that have been and need to be undertaken include intensification strategies—such as strengthening tax collection administration, supervision, and increasing the capacity of the apparatus—and extensification strategies through the development of new sources of revenue such as the tourism sector, kiosks/MSMEs, and the potential of forest products. The largest contributor to PAD to date is restaurant tax, while data on regional levies is not yet available.